New schools for a new century : the redesign of urban education - Ravitch, Diane; Viteritti, Joseph P., 1946- (Yale University Press, 1997)
In this book, distinguished scholars discuss recent controversial innovations - charter schools, contracting arrangements, and choice - designed to liberate educators from burdensome bureaucratic controls and raise the level of opportunity for all children. The authors focus on the problems in cities, where far too many children have been denied access to quality institutions. Various essays explore the lessons to be learned from Catholic schools, site-based management, and private entrepreneurs, as well as specific developments in three cities - New York, Milwaukee, and Chicago. The contributors, though realistic about the political and institutional obstacles that stand in the way of meaningful change, foresee the demise of the "one size fits all" approach to schooling. They envision a system of schools that is dynamic, diverse, performance-based, and accountable - one that is supportive of professionals, responsive to creativity, intolerant of failure, and committed to high educational standards for all children